Study of the tractive resistance of the no-till planting section - Shepelev Sergey; Pyataev M.; Kravchenko E. (FME Transactions, 2022)
The paper presents the results of studying the tractive resistance of the combined sowing section for no-till technology-based seeding. The sowing section consists of a slotting disk, an anchor colter, and a press wheel. To ensure the stability of the colter motion, the section has a parallelogram suspension and a balancing wheel with an adjustable vertical force acting on it, depending on the soil resistivity and the tilling depth. The sowing section ensures that the seeds are sown at a given depth in a moistened soil layer according to the agrotechnical requirements. Based on the theoretical studies, an analytical dependence was obtained, which allows for determining the tractive resistance of individual tools and the sowing section, depending on the design and operating parameters. The paper presents the results of the experimental studies on the dynamometer testing of the sowing section in laboratory conditions. To this end, an analog-digital measuring and computing complex and a software suite were used for the experimental data's post-experimental processing. Experimental dependences of the tractive resistance of individual tools and the sowing section, in general, were obtained, confirming the theoretical studies' correctness. The nominal tractive force of tractors was approximately determined, and the results of laboratory-field and field experiments with the sowing complex were presented.